Which Institutions Promote Growth? Revisiting the Evidence1. Issue 1 (24th February 2016) - Das, Kuntal; Quirk, Thomas
Abstract : Recent research examining the growth impacts of institutions have found that institutions are important in fostering economic growth. By building a framework around the institutional taxonomy proposed by Rodrik (2005), our paper contributes to the literature in the following way. First, we confirm the result that "institutions matter" and show that different types of institutions matter differently for growth. By applying a dynamic panel model, we find that market‐creating and market‐stabilising institutions are important in fostering economic growth. We then extend this analysis and investigate whether countries at different levels of development could respond heterogeneously to changes in their institutional structure. We find that poor countries benefit the most from market‐creating institutions and institutions that support market stability. We also find some evidence that market‐legitimising institutions such as "democracy" are not necessarily optimal for growth in poor countries. These results have important implications for countries that decide on the optimal strategy to improve their institutional framework.